The Relationship Between Body Mass Index (BMI) And The Incidence Of Primary Dysmenorrhea Among Female Adolescents At La Tansa 2 Senior High School In 2025 - Aminah Aminah; Farhah Khairunnisa (International Journal of Health Engineering and Technology, 2026)
Dysmenorrhea is menstrual pain that is often experienced by adolescent girls and can interfere with daily activities. One factor that is thought to be related to dysmenorrhea is Body Mass Index (BMI), because being underweight or overweight can affect the balance of reproductive hormones. This study aims to determine the relationship between Body Mass Index (BMI) and the incidence of dysmenorrhea in adolescent girls at La Tansa 2 High School. This study used a descriptive analytical design with a cross-sectional approach. The study population consisted of all female students at La Tansa 2 High School who were menstruating, with a simple size of 77 respondents using total sampling that met the inclusion criteria. Data were collected through questionnaires and measurements of weight and height to determine BMI. Data analysis was performed using univariate and bivariate analysis with the chi-square test. The results showed that of 77 respondents, 34 respondents (44.2%) had abnormal nutritional status, including underweight, overweight, and obesity. Of those with the abnormal nutritional status, 25 respondents (73.5%) experienced dysmenorrhea. Based on the chi-square results, a p-value of 0.568 (p> 0.05) was obtained, indicating no significant relationship between Body Mass Index (BMI) and the incidence of dysmenorrhea among female adolescent at La Tansa High School in 2025. In conclusion, there is no significant relationship between Body Mass Index (BMI) and the occurrence of dysmenorrhea among female adolescent at SMA La Tansa 2 in 2025. It is hoped that female adolescent will continue to manage stress and maintain a balanced diet to help reduce dysmenorrhea complaints.